2023
DOI: 10.3390/rs15051457
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning in the Classification of Soybean Genotypes for Primary Macronutrients’ Content Using UAV–Multispectral Sensor

Abstract: Using spectral data to quantify nitrogen (N), phosphorus (P), and potassium (K) contents in soybean plants can help breeding programs develop fertilizer-efficient genotypes. Employing machine learning (ML) techniques to classify these genotypes according to their nutritional content makes the analyses performed in the programs even faster and more reliable. Thus, the objective of this study was to find the best ML algorithm(s) and input configurations in the classification of soybean genotypes for higher N, P,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…The authors of [47] found high accuracy values in the classification of diseased and healthy leaves by using the SVM algorithm, similarly to [44], who used LR to find a disease detection model. The SVM has been proven to be an effective algorithm in several classification tasks, such as classifying soybean genotypes regarding the primary macronutrient contents [48] and classifying soybean genotypes according to their content of industrial grain parameters [10]. In both studies, using the raw information provided by the sensor guaranteed better results for the algorithm.…”
Section: Discussionmentioning
confidence: 99%
“…The authors of [47] found high accuracy values in the classification of diseased and healthy leaves by using the SVM algorithm, similarly to [44], who used LR to find a disease detection model. The SVM has been proven to be an effective algorithm in several classification tasks, such as classifying soybean genotypes regarding the primary macronutrient contents [48] and classifying soybean genotypes according to their content of industrial grain parameters [10]. In both studies, using the raw information provided by the sensor guaranteed better results for the algorithm.…”
Section: Discussionmentioning
confidence: 99%
“…The formed clusters were used as output variables, while the spectral data were used as input variables for the following classification models in the machine learning analyses: Multilayer Perceptron Artificial Neural Network (ANN, [27]), REPTree Decision Tree Algorithm (DT, [28]), J48 Decision Tree Algorithm (J48, [29]), Logistic Regression (LR, [30]), random forest (RF, [31]), and Support Vector Machine (SVM, [32]). The algorithms were chosen according to those most recently used in the literature [16,33,34]. The inputs tested in the datasets were spectral bands (SBs), vegetation indices (VIs), and the combination of both VIs+SBs.…”
Section: Methodsmentioning
confidence: 99%
“…In recent literature, there are works that use ML techniques together with multispectral data for various activities linked to phenotyping, such as [14] using leaf reflectance to classify soybean genotypes in terms of industrial characters, reaching levels of correct classification close to 0.9 [15]. Due to these applications, the use of such technologies can be promising in classifying soybean genotypes efficient in nutrient absorption; Santana et al [16] managed to carry out such selection in soybeans for primary macronutrients, achieving greater precision with algorithms such as SVM and J48.…”
Section: Introductionmentioning
confidence: 99%
“…A random cross-validation sampling strategy with k-fold = 10 and 10 repetitions (total of 100 runs) was applied. This strategy was used to evaluate the performance of the six supervised machine learning models, as already reported in other studies [27][28][29]. All model parameters were set according to the default setting of the Weka 3.8.5 software.…”
Section: Machine Learning Models and Statistical Analysismentioning
confidence: 99%